Analisis Kompetensi Pustakawan Menuju World Class University: Studi Kasus Perpustakaan Universitas Negeri Padang - Angga Fajar Pratama; Elva Rahmah (Maktabatuna, 2025)
In an effort to realize the vision of becoming a World Class University, the Universitas Negeri Padang Library has undergone various positive transformations, especially in terms of physical changes in the form of building construction and library locations. The physical transformation was caused by non-physical changes, especially in improving the quality of human resources, namely librarians. This study aims to describe the competence of librarians in supporting the achievement of a World Class University in the Universitas Negeri Padang Library environment. The method used in this study is qualitative with a descriptive approach, while informants were selected spectrally using the purposive sampling method. Data collection was carried out by observation, interviews and documentation. The results of this study indicate that: (1) the core competence of librarians includes the basic abilities and skills that must be possessed by a librarian in order to carry out their duties and responsibilities professionally. This competence covers various aspects, namely management, development, and organizational aspects; (2) professional competence which includes knowledge of information sources, technology, management and research and the ability to implement this knowledge in information services; (3) individual competence includes attitudes and values that support work efficiency, communication skills, a spirit of continuous learning, and readiness to face challenges; and (4) the criteria for librarians state that the librarian profession demands special requirements in accordance with the field of work carried out